The destiny of open cluster NGC 6530: past and future - Delong Jia; Yu, Heng; Shao, Zhengyi; Lu, Li (arXiv.org, 2024)
Studying the structures of open clusters is crucial for understanding stellar evolution and galactic dynamics. Based on Gaia DR3 data, we apply the hierarchical clustering algorithm to a young open cluster NGC 6530 and group its members into 5 substructures. By linear tracing with the kinematic information of their members, we find that: Sub 1 is the core of the cluster. It is expanding slowly. Sub 2 consists of less bound members, which began escaping from the core about 0.78 Myr ago. Sub 3 is associated with a young star forming region. It will merge with the core after 0.72 Myr; Sub 4, as an outskirt group, is also moving towards the core, but won't end up falling in. While Sub 5 is composed of less-bound members with field contamination. This work reveals the complex internal structure and evolutionary trends of the cluster NGC 6530. It also shows the potential of the hierarchical clustering algorithm in star cluster structure analysis.